Molecular biomarkers for the prognosis of breast cancer: role of amino acid metabolism genes - Zhou, Yudong; Yu, Shibo; Zhu, Lizhe; Wang, Yalong; Duan, Chenglong; Li, Danni; Du, Jinsui; Zhang, Jiaqi; Zhang, Jianing; Ma, Ruichao; He, Jianjun; Ren, Yu; et al. (Journal of physiology and biochemistry, 2025)
The development of precise molecular biomarkers for breast cancer prognosis holds immense potential to improve treatment outcomes. This study aimed to investigate the role of amino acid metabolism genes as predictive markers for breast cancer prognosis and their association with the immune-tumour microenvironment. By employing advanced machine learning algorithms and bioinformatics analysis techniques, the impact of amino acid metabolism-related genes (AAMRGs) on the immune status and overall survival of patients with breast cancer was examined. An AAMRG-based risk model was established to assess the prognostic significance. Validated risk models (AIMP2, IYD, and QARS1) accurately predicted patient outcomes [1 y: 0.87 (0.96–0.78); 3 y: 0.82 (0.87–0.76); 5 y: 0.80 (0.86–0.75)]. Furthermore, this study revealed evidence suggesting that QARS1 may influence breast cancer cell proliferation through methionine metabolism. This analysis provides valuable insights into the mechanisms of breast cancer, emphasizing the significance of AAMRGs as prognostic biomarkers and potential therapeutic targets for optimizing personalized treatment strategies. Key points The development of precise molecular biomarkers for the prognosis of patients with breast cancer holds immense potential in enhancing the outcomes of breast cancer treatment. This study employed machine learning algorithms and bioinformatics analysis techniques to conduct a comprehensive examination of AAMRGs and their impact on the immune status and overall survival of patients with breast cancer. A risk model predicated on AAMRGs was developed to assess their prognostic significance and could markedly bolster the personalized treatment approach for patients with breast cancer.